Nature of the chemical bond from the point of view of the degree of overlapping of electron shells for ions, atoms, and molecules - Zhyganiuk, I.V. (Reports of the National Academy of Sciences of Ukraine, 2016)
A physical criterion for covalent, ionis, and hydrogen bonds is constructed. The overlapping degree Δ for electron shells in compounds and complexes with covalent and ionic bonds is analyzed. It is shown that the density eΔ of the interaction energy per unit interval for ionic compounds is approximately more by the order of magnitude in comparison with that for covalent ones. This means that eΔ can serve as an adequate criterion for the description of the bond type. Analyzing the water dimer properties, it is shown that the value of eΔ for them takes the same order of magnitude as for halogenides of alkaline metals. At the same time, the overlapping degree for electron shells of water molecules forming a dimer in rarefied water vapor, Δ = 0.01, is close to that for an artificial instable molecule Ne2. These facts testify to the electrostatic character of the intermolecular interaction between water molecules belonging to a dimer with the main contribution given by the dipole-dipole forces.